2022
DOI: 10.1021/acsaem.2c01758
|View full text |Cite
|
Sign up to set email alerts
|

Toward Hot Carrier Extraction in Intervalley Photovoltaic Devices

Abstract: InGaAs heterostructures have demonstrated the means to maintain high energy '"hot" carrier behavior under practical operating conditions via transfer to upper valleys of the band structure, potentially decreasing thermalization losses in solar cells if a suitable extraction mechanism is developed. A set of four InGaAs heterostructures with altered n + top layers enable comparative analysis of the current density−voltage characterization and the relationship to the band and valley alignments. This reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…16 Recently, it has been shown that InGaAs/InAlAs heterostructured designs have promising applications in valley-photovoltaic solar cells. 33,34 However, the NW design of such compounds exhibit polytypism (intermixing of zinc-blende and wurtzite crystals) commonly observed in most III−V semiconductor NWs. 35,36 Our studies are enabled by realizing high-uniformity arrays of selective-area grown (SAG) InGaAs NWs passivated by thin epitaxial InAlAs shells, where wide tunability in size dimension (NW diameter) is achieved by accurately tuning the geometry of the SAG pattern.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recently, it has been shown that InGaAs/InAlAs heterostructured designs have promising applications in valley-photovoltaic solar cells. 33,34 However, the NW design of such compounds exhibit polytypism (intermixing of zinc-blende and wurtzite crystals) commonly observed in most III−V semiconductor NWs. 35,36 Our studies are enabled by realizing high-uniformity arrays of selective-area grown (SAG) InGaAs NWs passivated by thin epitaxial InAlAs shells, where wide tunability in size dimension (NW diameter) is achieved by accurately tuning the geometry of the SAG pattern.…”
Section: ■ Introductionmentioning
confidence: 99%
“…InGaAs NWs are among the most appealing candidate materials due to their tunable bandgap, especially toward 0.7 eV, which is the optimum bandgap energy of HCSCs with a relatively small thermalization coefficient (50 W/(K·cm 2 )), high carrier mobility, and high absorption coefficient . Recently, it has been shown that InGaAs/InAlAs heterostructured designs have promising applications in valley-photovoltaic solar cells. , However, the NW design of such compounds exhibit polytypism (intermixing of zinc-blende and wurtzite crystals) commonly observed in most III–V semiconductor NWs. , Our studies are enabled by realizing high-uniformity arrays of selective-area grown (SAG) InGaAs NWs passivated by thin epitaxial InAlAs shells, where wide tunability in size dimension (NW diameter) is achieved by accurately tuning the geometry of the SAG pattern. The hot carrier properties of the NW arrays are assessed by photoluminescence (PL) spectroscopy, and the temperature of hot carriers is determined by analyzing the PL spectra using the generalized Planck’s radiation law while taking the diameter-dependent photoabsorption of individual arrays into account.…”
Section: Introductionmentioning
confidence: 99%